The Impact Of Education, Training, And Work Experience Programs On The Work Productivity Of Nias Police Laka Lantas Unit Personnel - Kurnia Putera Bawamenewi; Eliagus Telaumbanua (UNIVED Press, 2025)
This study uses a quantitative approach to examine the relationship between the variables of education, training, and work experience on work productivity in the Nias Resort Police. The research sample consisted of 35 police personnel who were randomly selected from a total population of 349 personnel. Data was collected through questionnaires and analyzed using descriptive and inferential statistical techniques using SPSS Version 29 Software. The results of the analysis showed that there was a strong relationship between educational variables and work productivity, which was supported by a statistically significant regression coefficient value. The coefficient of determination (R Square) of 0.504 shows that about 50.4% of the variability in work productivity can be explained by the independent variables in this model. The F-statistical test showed that the regression model was significant overall at a 95% confidence level, with the rejection of the null hypothesis stating that there was no influence of independent variables on dependent variables. In addition, individual t-tests showed that only the educational variables significantly affected work productivity, while the training and work experience variables did not make a significant contribution. This research provides an in-depth understanding of the factors that affect work productivity in the police environment, with implications for the development of more effective managerial policies and practices in improving personnel performance.